Geomorphic change cause of spatial dynamics at Kendari Bay area - Makkawaru, Andi; Sukiyah, Emi; Sufrianto, Sufrianto (Edelweiss Applied Science and Technology, 2025)
Remote sensing systems have developed very well nowadays. Previously, it was very difficult to observe geomorphological changes due to the high cost of terrestrial mapping. Approaches through remote sensing are very helpful, especially in observing geomorphological changes, both natural and as a result of current human activities. In this paper, the discussion will focus on the elements of geomorphological change observed from a morphometric perspective, which are derived from remote sensing imagery. Assisted by model analysis from digital elevation models and quantitative interpretation of remote sensing images in the study area, it shows that the morphometric landscape of the study area has experienced significant erosion, with a hypsometric integral (Hi) value of 0.12. There are two sub-watersheds in the Kendari Bay area, which are circular (Rc > 0.5) and elongated (Rc < 0.5). The elongated watershed occupies the northern part of Kendari Bay, while the circular watershed is located in the southern part. In the circular watershed, there are fluvial geomorphological units, and in the estuary, there are wet plains and several flood plains. Based on multisensor analysis of Landsat images using the MNDWI method, a landscape change was observed in the Gulf estuary area from 2001 to 2019. The wet area in Kendari, where the wet plains in 2001 covered 185.56 hectares, has significantly shrunk to only 39.06 hectares in 2019. This land use change has disrupted the function of the estuary landscape as a water catchment area, which, if not addressed, could lead to problems such as flooding and sedimentation in Kendari Bay.